THE STRATEGY OF KODAM V BRAWIJAYA AND THE EAST JAVA PROVINCIAL GOVERNMENT IN FORMING CHARACTER EDUCATION IN SUPPORTING THE REALIZATION OF NATIONAL DEVELOPMENT IN THE FIELD OF EDUCATION AT SMA 5 TARUNA BRAWIJAYA - Yani Dhian Maulana (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study aims to analyze the implementation of educational integration between educational components organized by the East Java Education Office and the addition of national character education organized by Kodam V Brawijaya at SMA Negeri 5 Taruna Brawijaya. The objects of the study were Teachers and Students at SMA 5 Taruna Brawijaya, Kediri City. The method used in this study is a qualitative research method with a case study approach. The analysis technique used is SWOT Analysis and collecting data in the form of phenomena from Teachers and Students at SMA 5 Taruna Brawijaya, Kediri City. The results of the study prove that the implementation of educational integration between educational components organized by the East Java Education Office and the addition of national character education organized by Kodam V Brawijaya at SMA Negeri 5 Taruna Brawijaya has a positive and significant influence on improving the character of love for the homeland and nationality of students. The existence of real actions towards improving the behavior and character of nationality of students aims to instill a sense of love for the homeland and national insight of students. As students who have received and paid attention to education from parents and teachers at school, they will be able to think maturely and develop well, especially for students who have been guided, fostered and directed by their teachers at school. It is hoped that they will behave well in accordance with the student's personality.